Analisis pengendalian kualitas refined bleached deodorized palm kernel oil menggunakan metode Quality Loss Function di PT. ABC - Pasaribu, Hanna Christine; Yudisha, Nabila; Gunawan, Indra (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2023)
This study uses the Quality Loss Function as a way to see product variations on production costs. Quality Loss Function int is also used to indicate that a product or service is related to quality based on standards. Function of quality loss describes the functional relationship between deviation and loss, and it is usually used to assess the direct relationship between quality loss and damage in a refinery production process. From the results of data analysis and processing of data on the two parameters of color and FFA it is that the biggest cause of product damage is material factors,this is due to the fact that there are still many raw materials that do not comply with the parameters that have been set. From the results of research on RBDPKO products, for the cost of product repairs borne by companies with quality characteristics of smaller the better type is Rp. 743.719.690,62.